Unconditional convergence in the Mexican manufacturing sector (1988-2018) - Alex Rivadeneira (Banco de México, 2023)
In this paper, I document the existence of unconditional convergence in labor productivity across Mexican states in three-digit manufacturing industries. The rate of convergence for the period 1988-2018 is 1.18% per year. However, this result does not hold at the aggregate level: I find no unconditional convergence in manufacturing-wide labor productivity across states. Shift-sharing analysis reveals that the primary reason for this is the lack of labor reallocation towards more productive industries, and the underperformance of some of the largest ones. Unconditional convergence at all levels only occurred during 1988-1998. Afterward, the convergence process broke down and was only observed at disaggregated levels. I provide evidence that one possible cause of this breakdown is the socalled ''China shock". Additionally, I show that the convergence process, when it happened, has tended to exhibit a catching-down feature, where past-leaders have seen their labor productivity decline.
Keywords: O40; O14; O54; 330; Growth; Convergence; Manufacturing; Mexico